2019
DOI: 10.3390/antibiotics8030101
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Synergism of Colistin and N-acetylcysteine against Stenotrophomonas maltophilia

Abstract: Stenotrophomonas maltophilia is an emerging global opportunistic pathogen, responsible for a wide range of human infections, including respiratory tract infections. Intrinsic multidrug resistance and propensity to form biofilms make S. maltophilia infections recalcitrant to treatment. Colistin is among the second-line options in case of difficult-to-treat S. maltophilia infections, with the advantage of being also administrable by nebulization. We investigated the potential synergism of colistin in combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 36 publications
2
24
1
Order By: Relevance
“…However, it is known that organisms such as S. maltophilia actually grow in the form of biofilms that are more resistant to bacteria than bacteria floating on airway epithelial cells. 8,36,37 Previous research showed levofloxacin prevented biofilm formation of S. maltophilia isolates, 38 however, according to our study, a refractory infection in pleural effusion was caused by S. maltophilia with high biofilm production, characterized by resistance to SXT, LVX, and ceftazidime. 11 The patient was treated using TGC at first, however, the effect was not good, and biofilm production in the isolates may have contributed to the poor efficacy.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…However, it is known that organisms such as S. maltophilia actually grow in the form of biofilms that are more resistant to bacteria than bacteria floating on airway epithelial cells. 8,36,37 Previous research showed levofloxacin prevented biofilm formation of S. maltophilia isolates, 38 however, according to our study, a refractory infection in pleural effusion was caused by S. maltophilia with high biofilm production, characterized by resistance to SXT, LVX, and ceftazidime. 11 The patient was treated using TGC at first, however, the effect was not good, and biofilm production in the isolates may have contributed to the poor efficacy.…”
Section: Discussioncontrasting
confidence: 43%
“…However, it is known that organisms such as S. maltophilia actually grow in the form of biofilms that are more resistant to bacteria than bacteria floating on airway epithelial cells. 8 , 36 , 37 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ciacci et al demonstrated that N-acetylcysteine, in combination with colistin at concentrations likely achievable by topical administration, might represents a valid alternative for the treatment of respiratory infections caused by Stenotrophomonas maltophilia. Results from this study are very exciting, given the major role of S. maltophilia in difficult-to-treat respiratory tract infections in cystic fibrosis patients and, at the same time, the possibility to administer these two compounds via inhalation, likely reaching concentrations above the minimum inhibitory concentration (MIC) [10]. On the other hand, Richter et al showed the growth inhibitory effect of colistin plus chlorophyllin against Escherichia coli and Salmonella typhimurium.…”
mentioning
confidence: 90%
“…Other contributions showed a remarkable antimicrobial effect, alone or in synergy with standard antibiotics, of some well-known agents that are generally regarded as non-toxic, such as lactic acid, N-acetylcysteine, and chlorophyllin [9][10][11], thus providing very interesting examples of possible drug repositioning. Specifically, Bardhan and colleagues reported on the antimicrobial activity of lactic acid, a natural product often present in naturally fermented substances, against MDR and carbapenem-resistant clinical strains of K. pneumoniae.…”
mentioning
confidence: 99%